Gambaran Pengetahuan Masyarakat Tentang Vaksinasi Covid-19 di Puskesmas Sidomulyo Kecamatan Tampan Kota Pekanbaru - Riski Ridho Ramadani; Bayu Saputra; Rani Lisa Indra (LPPM Hang Tuah Pekanbaru, 2023)
The spread of COVID-19 has not only attacked globally but has also reached Indonesia. COVID-19 has spread to provinces in the territory of Indonesia, including Riau Province. One way to prevent COVID-19 is to carry out the COVID-19 vaccination. The purpose of this study was to describe the public's knowledge of COVID-19 vaccination. This study uses a type of quantitative research. The population used by the researcher was 361 people. The sample of this study used 177 respondents. The sampling technique used is Consecutive Sampling. The research instrument was carried out using a questionnaire. Data analysis was carried out by using the univariate method, while on the characteristics of respondents, age used a numerical test, gender, education, occupation, and socioeconomic used a frequency distribution. the results of the study showed that the average age was 33.2 years, the majority of respondents were female as much as 80.8%, the majority of secondary education levels were education (SMA/SMK equivalent) as much as 79.7%, the majority of respondents worked as housewives (IRT) as much as 75.1%, the majority of the socioeconomic level is classified as low level as much as 54.2%. Respondents' knowledge about COVID-19 vaccination, most of the respondents still have a low level of knowledge about COVID vaccination as much as 44.5%, so it can be concluded that knowledge at the Sidomulyo Health Center is still in the low category.